In vitro antioxidant and neuroprotective activity of green tea and papaya leaf formulation mediated silver nanoparticles - Priyanka Sivasubramanian; Subramanian R M; Joshitha Subramaniam; Parameswari Royapuram Parthasarathy (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by oxidative stress, amyloid-beta (Aβ) aggregation, and cholinergic dysfunction. Plant-mediated synthesis of silver nanoparticles (AgNPs) offers a biocompatible approach to target these pathological features. This study investigates the antioxidant, acetylcholinesterase (AChE) inhibitory, and amyloid (Aβ1–42) aggregation inhibitory properties of AgNPs synthesized using green tea and papaya leaf extracts, with a focus on their potential neuroprotective effects. Methodology: Silver nanoparticles were synthesized using green tea and papaya leaf extracts. The antioxidant activity of the AgNPs was assessed using DPPH and ABTS radical scavenging assays. The synthesized AgNPs were tested at varying concentrations (5–160 µg/mL) in all assays, and ascorbic acid was used as a standard antioxidant. The AChE inhibitory activity was evaluated using Ellman’s method, while the anti-amyloid activity was measured by examining the inhibition of Aβ1–42 peptide aggregation. Results: The AgNPs exhibited significant antioxidant activity, with DPPH inhibition reaching up to 89.85% and ABTS inhibition up to 85.43% at the highest concentration. The AChE inhibitory activity demonstrated concentration-dependent inhibition, with a maximum inhibition of 79.93% at 160 µg/mL. Furthermore, the AgNPs effectively inhibited Aβ1–42 aggregation, with only19.2% aggregation observed at 100µg/mL. The bioactivity of AgNPs is attributed to the polyphenolic compounds present in green tea and papaya leaf extracts, enhancing their neuroprotective properties. Conclusion: The AgNPs synthesized from green tea and papaya leaf extracts demonstrated potent antioxidant, AChE inhibitory, and anti-amyloid aggregation activities, making them promising candidates for therapeutic applications in Alzheimer’s disease. These findings support the potential of plant-mediated AgNPs as multifunctional agents in targeting key pathological mechanisms of AD, with future studies needed to explore their in vivo efficacy and mechanisms of action.